(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aimed to analyze the publications about the effect of the software geogebra on the mathematical competences in high school students in the last decade. The final sample includes 17 articles and followed the methodology proposed by the PRISMA Declaration. The results show that the geogebra software has been a determining factor in the development of mathematical competencies, with emphasis on mathematical understanding, geometric reasoning and problem solving. Additionally, the geogebra software produces significant effects in contrast with traditional instruction. Thus, this review addresses the use of geogebra software as a resource to develop mathematical competencies in high school students.